Bihemispheric Motor Cortex Transcranial Direct Current Stimulation Improves Force Steadiness in Post-Stroke Hemiparetic Patients: A Randomized Crossover Controlled Trial - Montenegro, Rafael A.; Midgley, Adrian; Massaferri, Renato; Bernardes, Wendell; Okano, Alexandre H.; Farinatti, Paulo (Frontiers in Human Neuroscience, 2016)
Post-stroke patients usually exhibit reduced peak muscular torque (PT) and/or force steadiness during submaximal exercise. Brain stimulation techniques have been proposed to improve neural plasticity and help to restore motor performance in post-stroke patients. The present study compared the effects of bihemispheric motor cortex transcranial direct current stimulation (tDCS) on PT and force steadiness during maximal and submaximal resistance exercise performed by post-stroke patients vs. healthy controls. A double-blind randomized crossover controlled trial (identification number: TCTR20151112001; URL: http://www.clinicaltrials.in.th/) was conducted involving nine healthy and ten post-stroke hemiparetic individuals who received either tDCS (2 mA) or sham stimulus upon motor cortex for 20 min. PT and force steadiness (reflected by the coefficient of variation of muscular torque) were assessed during unilateral knee extension and flexion at maximal and submaximal workloads (1 set of 3 reps at 100% PT and 2 sets of 10 repetitions at 50% PT, respectively). No significant change in PT was observed in post-stroke and healthy subjects. Force steadiness during knee extension (~25-35%, P<0.001) and flexion (~22-33%, P<0.001) improved after tDCS compared to the sham condition in post-stroke patients, but improved only during knee extension (~13-27%, P<0.001) in healthy controls. These results suggest that tDCS may improve force steadiness, but not PT in post-stroke hemiparetic patients, which might be relevant in the context of motor rehabilitation programs.